2017
DOI: 10.1159/000479383
|View full text |Cite
|
Sign up to set email alerts
|

A High Fat Diet During Pregnancy and Lactation Induces Cardiac and Renal Abnormalities in GLUT4 +/- Male Mice

Abstract: Background/Aims: Altered nutrients during the in utero (IU) and/or lactation (L) period predispose offspring to cardio-renal diseases in adulthood. This study investigates the effect of a high fat diet (HFD) fed to female mice during IU/L on gene expression patterns associated with heart and kidney failure and hypertension in male offspring. Methods: Female wild type (WT) mice were fed either a HFD or control chow (C) prior to mating with males with a genetic heterozygous deletion of GLUT4 (G4+/-, a model of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
5
1
Order By: Relevance
“…Studies have shown that an interaction between maternal high fat diet and the genotype during early life development can enhance the susceptibility to cardio-renal diseases later in life, hence potentiating the need to discourage or limit unhealthy snacking among pregnant women. [ 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that an interaction between maternal high fat diet and the genotype during early life development can enhance the susceptibility to cardio-renal diseases later in life, hence potentiating the need to discourage or limit unhealthy snacking among pregnant women. [ 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it is demonstrated by utilizing each of these models that there are overarching similarities by which IUGR offspring are predisposed to CVRD, which supports the developmental programming of chronic disease. IUGR offspring from many of these models have altered cardiomyocyte biology, including early reductions in cardiomyocyte numbers reported in offspring from dams with bilateral uterine ligation (30), decreased cardiomyocyte proliferation by postnatal day 1 in offspring of dams with maternal hypoxia (171), decreased cardiac expression of genes involved in heart's ability to produce energy from fatty acid oxidation in mice offspring exposed to maternal HFD by 27 wk of age (112), and increased contractile function of isolated left ventricles by 12 wk of age in offspring from nutrient-restricted dams (80). Moreover, data from these various models of developmental programming of CVRD in IUGR offspring show reductions in nephron endowment.…”
Section: Experimental Models Of Iugrmentioning
confidence: 99%
“…It has been reported that a high-fat diet, given during pregnancy and lactation in mice, could increase heart and kidney weight and reduce cardiac insulin responsiveness, expanding the risk of cardiorenal diseases in male mice [26]. However, our results showed the heart weight was more affected by the post-weaning diet (p = 8.84 × 10 −6 ) than the litter size (p = 0.009), not showing any significant effect of the maternal diet (p = 0.26).…”
Section: Discussionmentioning
confidence: 99%